2006
DOI: 10.1108/09513550610658231
|View full text |Cite
|
Sign up to set email alerts
|

Au revoirto partnerships: what's next ?

Abstract: PurposeTo review the current debates on partnership working and to examine whether a “fitness for purpose” test is an appropriate way of evaluating existing developments.Design/methodology/approachThe paper examines the conceptual frameworks within which the partnership discourse has been located, and reflects on whether this enables both practitioners and academics to make sense of the partnership literature and arrangements.FindingsThe paper argues that existing frameworks are limited and suggests that alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 6 publications
3
30
0
Order By: Relevance
“…Nevertheless, even this literature largely does not provide substantial guidance or learning that could be widely beneficial to enable policy-makers and practitioners to improve collaboration Glasby 2010, McGuire andAgranoff 2011). This limitation is all the more galling as, despite the indications of lack of impact and the possibility that collaboration 'fatigue' (Diamond 2006) developed through the period of the Labour government, 'policy makers and professionals remain so attached to [collaboration] as an idea' (Sullivan 2010, p. 19). …”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, even this literature largely does not provide substantial guidance or learning that could be widely beneficial to enable policy-makers and practitioners to improve collaboration Glasby 2010, McGuire andAgranoff 2011). This limitation is all the more galling as, despite the indications of lack of impact and the possibility that collaboration 'fatigue' (Diamond 2006) developed through the period of the Labour government, 'policy makers and professionals remain so attached to [collaboration] as an idea' (Sullivan 2010, p. 19). …”
Section: Introductionmentioning
confidence: 99%
“…pg4). However, this a priori assumption of partnerships as a 'good thing' -which resonates throughout studies of partnership working (Diamond, 2006;Sullivan & Skelcher, 2002) -can create a false basis on which to work and a false sense of proximity between partnering organisations particularly given widely recognised, long-standing difficulties between agencies -elsewhere this has been considered an "uncritical acceptance" of partnership policies (Dickinson & Glasby, 2010). Reflecting on the experience in Glasgow, one senior manager in a parent organisation described this state as a "cloud of slightly ill defined optimism..." (SenHealth Intv.pg4).…”
Section: Mind the Gapsmentioning
confidence: 99%
“…Partnership working has been enshrined in public policy in the UK for many years (Diamond, 2006) and its rationale rehearsed in policy and academic publications. In many respects, partnership is an organising form that sits somewhere between markets and hierarchies (Jackson & Stainsby, 2000) although the term 'partnership' has come to be used in so many inconsistent ways, that it can often also be used to describe more market-based types of interaction (Dickinson & Glasby, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…It is suggested that local government are of the view that high-quality services, delivered by local partnerships characterised by high levels of user and community participation, are the best means of ensuring that disadvantaged groups are socially included (Ellison and Ellison, 2006). This transfer to partnership has created significantly new modes of leisure service delivery yet there is a need to examine and reflect upon the implications these models present (Diamond, 2006). The interest of this research, then, is to investigate social inclusion across different modes of public leisure provision in the context of on-going governmental concerns for social inclusion in an environment of increasing budgetary cuts.…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with public management reforms across Europe in an attempt to get public sector organisations to function more effectively (e.g., Turrini et al, 2010). Collaboration between the public, private and voluntary sectors was subsequently promoted under New Labour in leisure service delivery (Diamond, 2006). It is suggested that local government are of the view that high-quality services, delivered by local partnerships characterised by high levels of user and community participation, are the best means of ensuring that disadvantaged groups are socially included (Ellison and Ellison, 2006).…”
Section: Introductionmentioning
confidence: 99%